Code Drawings in Hopscotch. - Fajardo, Rafael (Reconstruction: Studies in Contemporary Culture, 2016)
The article explores the code drawings created in Hopscotch, a visual programming environment available on electronics company Apple's iOS for the Apple iPad computer tablet intended for young learners.